"Quitting like a Turk:" How political priority developed for tobacco control in Turkey. (September 2016) - Hoe, Connie; Rodriguez, Daniela C.; Üzümcüoğlu, Yeşim; Hyder, Adnan A.
Abstract: In recent years, tobacco control emerged as a political priority in Turkey and today the country is widely regarded as one of the global leaders in tackling tobacco use. Although political priority is considered a facilitating factor to the success of addressing public health issues, there is a paucity of research to help us understand how it is developed in middle-income countries. The primary aim of this study is to understand the process and determinants of how tobacco control became a political priority in Turkey using the Multiple Streams Framework . A mixed-methods case study approach was used whereby data were gathered from three different sources: in-depth interviews (N = 19), document reviews (N = 216), and online self-administered surveys (N = 61). Qualitative data were collected for the purpose of understanding the processes and determinants that led to political prioritization of tobacco control and were analyzed using deductive and inductive coding. Quantitative data were collected to examine the actors and were analyzed using descriptive statistics and network nominations. Data were triangulated. Findings revealed that tobacco control achieved political priority in Turkey as a result of the development and convergence of multiple streams, including a fourth, separate global stream. Findings also shed light on the importance of Turkey's foreign policy in the transformation of the political stream. The country's desire for European Union accession and global visibility helped generate a political environment that was receptive to global norms for tobacco control. A diverse but cohesive network of actors joined forces with global allies to capitalize on this opportunity. Results suggest (1) the importance of global-agenda setting activities on political priority development, (2) the utility of aligning public health and foreign policy goals and (3) the need to build a strong global incentive structure to help entice governments to take action on public health issues. Highlights: Process and determinants that led to prioritization of tobacco control were unveiled. A fourth "global stream" was found to be vital to the prioritization process. Results suggest the utility of aligning public health and foreign policy goals.